Gender, conflict, peace, and UNSC Resolution 1325 - Shekhawat, Seema (Lexington Books, 2018)
This book examines the position of women in formal peace making in the context of UNSC Resolution 1325. It asks if the resolution, passed seventeen years ago, has been consigned to the domain of rhetoric, or whether it still has practical significance.